Patient Safety in Microvascular Plastic Surgery - Colakoglu, Salih; Tebockhorst, Seth; Chong, Tae W.; Mathes, David W. (Journal of Reconstructive Microsurgery, 2019)
Patient safety is defined as freedom from accidental or preventable harm produced by medical care. The identification of patient- and procedure-related risk factors enables the surgical team to carry out prophylactic measures to reduce the rate of complications and adverse events.The purpose of this review is to identify the characteristics of patients, practitioners, and microvascular surgical procedures that place patients at risk for preventable harm, and to discuss evidence-based prevention practices that can potentially help to generate a culture of patient safety.
Keywords: patient safety; microsurgery; microvascular surgery; free flap